Interactions between Starch, Lipids, and Proteins in Foods: Microstructure Control for Glycemic Response Modulation. Issue 14 (25th October 2016) - Parada, Javier; Santos, Jose L.
Abstract : In real food, starch is usually forming part of a matrix with lipids and proteins. However, research on this ternary system and interactions between such food components has been scarce so far. The control of food microstructure is crucial to determine the product properties, including sensorial and nutritionals ones. This paper reviews the microstructural principles of interactions between starch, lipids, and proteins in foods as well as their effect on postprandial glycemic response, considering human intrinsic differences on postprandial glycemic responses. Several lines of research support the hypothesis that foods without rapidly digestible starch will not mandatorily generate the lowest postprandial glycemic response, highlighting that the full understanding of food microstructure, which modulates starch digestion, plays a key role on food design from a nutritional viewpoint.